Urusniaga Matawang Asing di Platform Forex Exchange Direct Dealer (FXDD): Satu Analisis Fiqh dan Transaksi Undang-Undang Islam - Mohd Zaki, Zainol (2012)
The issue of foreign exchange or forex arises when there is international trade transaction involving two countries which use different currencies. It becomes more critical and important in Islamic Muamalat when it involves Muslim foreign exchange traders. A review of the current literature has shown a difference in opinion among jurists and scholars in determining the permissibility of this transaction. This thesis discusses the contract (akad) and modus operandi of foreign currency transactions and its application in terms of using the internet Exchange Platform Forex Direct Dealer (FXDD). The discussion focuses on the legal debate about the types of contracts used, the use of hedging and leverage in forex by individuals according to the views of the jurists (fuqaha) who allow it and those who ban it. The objective of the study is assessing the validity of the contract of foreign currency transaction over the internet. In addition, it aIso aims to identi6 the difference between the principles of IsIamic transactions with the modus operandi used in foreign exchange transactions in the conventional market. The qualitative method was used to achieve the objectives of the study. Emphasis is given to the two types of survey research data forms, such as literature review, observation and interviews, and analysis of relevant data by using the deductive, inductive and comparative methods. The results of this study found that the types of contracts used in the forex trading platform Forex Exchange Direct Dealer (FXDD) is the contract in writing and is justified under Islamic Muamalat. The modus operandi of the sale and purchase contracts, hedging, leverage and swap in Forex platform Direct Exchange Dealer (FXDD) are also conducted according to the Islamic requirements for paper currency contract transactions which rely on the concept of alsar- The Principles contained in the concept of al-Sarf have been agreed upon by Muslim scholars.